Comparative Techno-Economic Evaluation of 5G mobile network deployments in different scale urban areas - Eleni Laitsou; Dimitris Katsianis (International Telecommunications Society (ITS), 2021)
Mobile communication technology is moving into the fifth-generation (5G) which is expected to overcome the new challenges that have emerged with the Internet of Things (IoT) and the exponential growth in demand for mobile traffic. Therefore, the Mobile Networks Operators (MNOs) are planning to improve their networks in order to achieve the required standards for capacity, coverage and quality of service. In this paper, a techno-economic study is performed to assess the feasibility of the deployment of a 5G mobile network in different types of urban areas depending on population density. In each of these different cases, the conditions are studied under which such an investment can be economically viable through increased revenues and reduced costs. The findings of this study could become an important tool for decision and policymakers in investment strategies for 5G mobile networks.
Keywords: 330; 5G mobile network; techno-economic evaluation; TONIC model; urban